أثر البوزولانا الطبيعية على ديمومة المنتجات المسبقة الصنع من الخرسانة المسلحة بالألياف الزجاجية GFRC - خيربك, علي; فاضل, عماد; تفاحة, سوزان (Latakia University Journal -Engineering Sciences Series, 2018)
بهدف تحسين ديمومة المنتجات المسبقة الصنع من الخرسانة المسلحة بالألياف الزجاجية، وضمن سياق تطبيقات الاستدامة والتقليل من استهلاك الاسمنت واستبداله بمواد خضراء، تم القيام بهذه الدراسة لاختبار دور البوزولانا الطبيعية المأخوذة من تل شيحان بالسويداء كمستبدل اسمنتي بنسب 10%- 15%- 20%- 25%، وتحديد تأثير كل من هذه النسب على قوام الخلطة ومقاومة الشد بالانعطاف على مدى 180 يوم، وكذلك اختبر دورها في تحسين البنية الداخلية للخلطة من خلال التقليل من محتوى Ca(OH)2 وزيادة C-S-H & C-A-S-H gel فيها، والذي اختبر باستخدام تقنيةX-Ray Diffraction (XRD) وتقنية Energy Dispersive X-Ray (EDX) الأمر الذي قلل بدوره من تهتك الألياف كما أظهرت الصور بالمجهر الالكتروني Scanning Electron Microscopy (SEM). وكذلك درس دور البوزولانا الطبيعية في السيطرة على التدهور الحاصل للمادة بمرور الزمن والذي اختبر من خلال الغمر بالماء الساخن بدرجة C 50º لمدة 150 يوم وبحلقات التجفيف – ترطيب، وتم أيضاً دراسة أثرها على الامتصاص والمسامية ومقاومة هجمات الكبريتات. أظهرت النتائج أنه ليس للبوزولانا الطبيعية المستخدمة أثر سلبي يذكر على قوام الخلطة أو على الخصائص الميكانيكية وتحسنت جميع عوامل الديمومة المدروسة. The aim of this study is improving the durability of precast products of Glass Fiber Reinforced Concrete (GRC) and in the context of sustainability applications, reduction of cement consumption and replacement of it with green materials. This study has been done to test the role of the natural pozzolan from Shihan Hill in As Suwayda as supplementary cementing material by 10% -15% -20% - 25%, and to determine the effect of it on the consistency and flexure strength over 180 days, as well as to test its role in improving the micro-structure of the mixture by reducing the content of Ca(OH)2 and increasing C-S-H & C-A-S-H gel, which were tested using X-Ray Diffraction (XRD) and Energy Dispersive X-Ray (EDX) techniques, and as a result reduced the erosion of fibers as shown in images by Scanning Electronic Electron Microscopy (SEM). Moreover the role of pozzolana has been studied in controlling the degradation of the material over time which tested by immersion in hot water 50° for 150 days and by drying – wetting cycles. Also the effect of pozzolana on absorption, porosity and resistance of sulfates attacks was studied. The results have shown that the used natural pozzolana has no negative effect on consistency or mechanical properties, and it improved all the studied durability factors.